Perceived fatherhood roles an instrument of adaptation in a post disaster setting - Muring, Edward J.; Pelias, Amiel Lyndon; Brazas-Lim, Ladylyn (2016)
Perceived gender roles play a big part in adapting to a post disaster setting. Whether it is economic or social, men and women base their actions and decisions on how they perceive their roles in their family and society. When men for example see themselves as the provider for their families then their priorities and decisions will be based around that assumption. With this, we are able to analyze the effects of climate change on both genders and examine their perspectives on adaptation priorities and strategies. This study will be centered on the male perspective of fishermen from Barangay 88 and how they adapted to resettlement in a completely different location from their place of origin.
This study incorporated the work of Allen Tan on Four Meanings of Fatherhood. The focus of this paper was on the male parent using the four typology which represented four different conceptions of the role of fathers in their family. The four typology of fatherhood is fundamentally based on two dimensions; activity and affective dimensions. According to Allen Tan (1994), the activity dimension refers to how active a man is as a father to his degree of involvement in the role of fatherhood. The affective dimension refers to the emotional tone of his involvement with the role; whether he positively relishes it or negatively disdains it. Combining these two dimensions, he arrived at a fourtold typology of fathers.
The results of the study revealed that there have been no change in the perception of fatherhood roles in the post disaster setting. In terms of the perceive role of fathers in the family, it has been determined that they fall to the procreator typology. They see themselves as the one mainly responsible for providing for the needs of their families. On the other hand, their perception on their children falls on the determinative type wherein they see their children as projects of themselves. Although there have been no change in their perception in the roles of the fathers, it is important to know that these perceptions have helped these fathers in adapting to these changes.
Undergraduate thesis (B.A.S.S. Political Science ) -- University of the Philippines, Tacloban.
Keywords: Social Sciences